PENGARUH METODE PEMBELAJARAN DAN PENGETAHUAN BERWAWASAN LINGKUNGAN TERHADAP KECERDASAN NATURALIS ANAK USIA DINI 5-6 TAHUN - Sumantri, Mohamad Syarif; Diana, Diana (JIV-Jurnal Ilmiah Visi, 2011)
The purpose of this research was to obtain the data on the effects of instructional methods and insightful knowledge of environment towards the naturalistic intelligence of the children at the age of five and six years. Employing experimental methods, this research was carried out in Natural Ar-Ridho Kindergarten, Semarang. The results of this research show (1) naturalistic intelligence of the children with hands-on learning method is higher than of those with storytelling method, (2)naturalistic intelligence of the children having insightful knowledge of environment and treated with hands-on method of learning is higher than those treated with storytelling method, (3) naturalistic intelligence of the children having low insightful knowledge of environment and treated with storytelling method is higher than those treated with hands-on learning methods and (4) there is interaction between instructional method and insightful knowledge of environment towards the naturalistic intelligence of the children at the age of five and six years